Investigation of prescribing trends and prescriptions for common diagnoses in primary care: Nationwide data of Turkey - AKICI, AHMET (CUKUROVA UNIV, FAC MEDICINE, 2020)
Purpose: This study aimed to examine the details of prescriptions issued in primary care and the changes over the years in Turkey. Materials and Methods: We analyzed all electronic prescriptions registered to Prescription Information System by primary care physicians in Turkey between 2013 and 2016. The mean number of drugs per prescription (nDPP) was determined by patients' sex and age groups. The percentages of the prescriptions containing the top twenty most frequently encountered drugs were determined for each year of the study. In the four-year period, the percentage of prescriptions with the ten most common diagnoses among prescriptions with single diagnosis and nDPP were examined. Results: A total of 1.457.034.275 drugs were prescribed in 518.335.821 prescriptions and nDPP was 2.81 for the four-year period. The most commonly used drugs in all prescriptions were other cold preparations (19.2-19.7%) and amoxicillin+beta-lactamase inhibitor (9.9-10.5%). The diagnosis of hypertension (6.9%, nDPP: 2.00) and acute upper respiratory tract infection, unspecified (URTI), (6.5%, nDPP: 2.61) were in the top ranks in single-diagnosis prescriptions during four-year period. Conclusion: Primary care prescriptions appear to be mostly generated for women and elderly populations, with a tendency for URTI and hypertension indications. Overprescriptions of cold preparations, NSAIDs, PPIs, analgesics, and broad-spectrum antibiotics imply existence of important problems in the primary care regarding rational prescribing behavior.
Keywords: Drug utilization; primary care; national data; electronic prescription; trend analysis; PREVENTION; ASPIRIN; MANAGEMENT; PATTERNS; ADULTS